Cancer immune control needs senescence induction by interferon-dependent cell cycle regulator pathways in tumours - Ellen Brenner (Nature Portfolio, 2020)
The growth of cancer cells can be stably arrested by cytokine-induced senescence. Here, the authors show that cancers with defects in senescence-inducing cell cycle regulator pathways are resistant to immune checkpoint blockade.